2021
DOI: 10.1371/journal.pone.0246510
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study on metabolite accumulation in a wild barley NAM population reveals natural variation in sugar metabolism

Abstract: Metabolites play a key role in plants as they are routing plant developmental processes and are involved in biotic and abiotic stress responses. Their analysis can offer important information on the underlying processes. Regarding plant breeding, metabolite concentrations can be used as biomarkers instead of or in addition to genetic markers to predict important phenotypic traits (metabolic prediction). In this study, we applied a genome-wide association study (GWAS) in a wild barley nested association mapping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…When studies were stratified into two larger groups, those with 0-60 CRC patients and those with 61+ patients (split so there would be roughly an equal number of studies in each group), studies with 61+ patients identified an average of 10 more metabolites, at p = 0.11. Variation of metabolites, in addition to sample size, together with differences in instrument, technique, and study population at different geographic locations (i.e., patients in Japan may have different metabolic profiles than those in America) might explain why different metabolites were identified by various studies [60].…”
Section: Evaluating the Performance Of Metabolomics-based Assays In Crc Studiesmentioning
confidence: 99%
“…When studies were stratified into two larger groups, those with 0-60 CRC patients and those with 61+ patients (split so there would be roughly an equal number of studies in each group), studies with 61+ patients identified an average of 10 more metabolites, at p = 0.11. Variation of metabolites, in addition to sample size, together with differences in instrument, technique, and study population at different geographic locations (i.e., patients in Japan may have different metabolic profiles than those in America) might explain why different metabolites were identified by various studies [60].…”
Section: Evaluating the Performance Of Metabolomics-based Assays In Crc Studiesmentioning
confidence: 99%
“…The sample size needed for the analysis varies depending on the concentration of the target metabolites, pretreatment techniques, and analytical techniques, but it commonly falls between 10 and 100 mg fresh weight. Controls for consistent sampling in a short period of time are necessary for large-scale sampling, such as that required for mGWAS investigations, because the metabolome is sensitive to environmental influences ( Gemmer et al., 2021 ; Yao et al., 2021 ). To prevent chemical changes caused by enzymatic and chemical reactions, a quenching method such liquid nitrogen freezing and extraction with organic solvents should be carried out right away.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In a barley RIL population, the mQTL study detected 98 different stress-responsive metabolites and observed that their abundance modulates through coordinated expression of several genes to function under drought conditions (Piasecka et al, 2017). A mQTL study, was applied in the large barley nested association mapping (NAM) population (Gemmer et al, 2021). Approximately 130 sugars and sugar-like metabolites were detected on ealry and late sampling dates.…”
Section: Biochemical and Metabolic-related Traitsmentioning
confidence: 99%